Kepemimpinan Pendidikan Visioner Dalam Mewujudkan Generasi Berkarakter - Rohimat Rohimat (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2024)
Character education is an important aspect in the formation of individuals with superior and moral personalities. Character education aims to foster positive values, discipline, responsibility, and social concern in students in order to be able to contribute constructively to the community and the surrounding environment. One of the important factors in the success of character education in schools is the visionary leadership of the principal. This research uses a qualitative approach with a type of case study that focuses on the visionary leadership of the principal of SMA Muhammadiyah Cikelet in developing the character of students in the school environment. The data sources in this study consist of school principals as the main informants, as well as teachers and education staff as supporting informants. Data was collected through in-depth interviews, field observations, and documentation. The results of the study show that the principal of SMA Muhammadiyah Cikelet has implemented visionary leadership effectively through the preparation of the school's vision and mission which is oriented towards the formation of religious character, discipline, and responsibility of students. The principal also plays a role as a motivator and role model, who is able to inspire and encourage all school residents, both teachers and students, to actively participate in creating a learning environment with character and noble character.